Economic Entrepreneurship, Startups and Their Effects on Local Development: The Case of Sweden - Hans Westlund; Amy Olsson (European Regional Science Association (ERSA), 2011)
The current empirical entrepreneurship literature mainly shows a positive correlation between entrepreneurship (measured as the number of startups) and economic growth. However, the mechanisms by which entrepreneurship exerts its positive influence are not obvious. The net result of startups on employment or GDP can be negative, at least in the short run, since efficient, new companies may lead to closures of less efficient ones. Based on an assumption that economic entrepreneurship in the form of startups creates unobserved supply side effects on the firm level (Fritsch & Mueller 2004) and entrepreneurial social capital on community level (Westlund & Bolton 2003) this paper studies the connections between startups and local development at the municipal level in Sweden between 2000 and 2008. We use a unique database including not only total startups, but data on startups divided in six branches to study the impact of entrepreneurship on population and employment growth. Analyses are performed on all municipalities as well as by municipality type and by growth rate.
Keywords: 330